Manual, Prosedur, dan Instruksi Kerja Proyek Kontinum Publikasi Artikel Ilmiah Mahasiswa - Susanti Vera; Putri Anditasari; Hidayatul Fikra; Fitriani Fitriani; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to discuss the design of manuals, procedures and work instructions for continuum projects. This research uses a qualitative approach by applying the Focus Group Discussion method. The results and discussion of the research show that input documents in the form of manual designs, procedures and work instructions for continuum projects are needed to ensure the process, output, outcomes, benefits and impact of continuum project implementation. This research concludes that manuals, procedures and work instructions are input documents in the continuum project framework.